2004
DOI: 10.1097/00001573-200403000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Genetic basis of congenital heart disease

Abstract: The information in this review provides insights into the state-of-the-art knowledge about the molecular genetic causes of congenital heart defects. It suggests that DNA testing may become standard for many forms of congenital heart defects, improving clinicians' ability to anticipate complications for their patients and predict recurrence risk for families of children with congenital heart defects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(38 citation statements)
references
References 29 publications
0
37
0
1
Order By: Relevance
“…Several genes have been identified as being responsible for various congenital heart diseases (23). It has been shown that mutations of most congenital heart diseases genes can engender more than one cardiac phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes have been identified as being responsible for various congenital heart diseases (23). It has been shown that mutations of most congenital heart diseases genes can engender more than one cardiac phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…(78,79) Both misalignment of cardiac regions and deficient tissue fusion cause heart malseptation, a frequent component of syndromic and non-syndromic congenital heart disease. (80) Another important tissue fusion event affects the development of the epicardium, the outermost layer of the heart, which develops once the single-looped heart tube primordium is formed. The epicardial progenitors are found in the proepicardium, a coelomic cell mass located at the caudalmost region of the heart tube.…”
Section: Development Of the Hypophysismentioning
confidence: 99%
“…The etiology of TOF is multifactorial, implying contributions from sequence variations, anomalous gene expression, and epigenetic factors, as well as environmental contributions. Functional mutations of several important cardiac-related transcriptional factor genes and chromosomal abnormality were identified in patients with TOF, supporting a genetic contribution (4)(5)(6). In spite of the expanding knowledge of the genetic mechanisms involved in cardiac formation, there remain nearly 80% of children with congenital heart defects who do not have a known genetic defect.…”
mentioning
confidence: 94%